Spatial analysis of mortality due to congenital syphilis in Brazil from 2008 to 2022 - Yago Tavares Pinheiro; Richardson Augusto Rosendo da Silva; Ketyllem Tayanne da Silva Costa; Angelo Giuseppe Roncalli da Costa Oliveira; Janmilli Dantas da Costa; Cristiane da Silva Ramos Marinho; Jurandir Alves de Freitas Filho; Luennia Kerlly Alves Rocha; Victória Sampaio Moreira; Ruan Carlos de Queiroz Monteiro; José Rebberty Rodrigo Holanda (PLoS ONE, 2026)
The objective of this study is to analyze spatial distribution of mortality due to congenital syphilis in Brazil from 2008 to 2022. This is an ecological study that considered congenital syphilis deaths reported in all Brazilian municipalities, from 2008 to 2022, available in the Brazilian government’s information systems. We built a thematic map to describe the distribution of congenital syphilis mortality in the country and, subsequently, applied the Local Index Spatial Analysis to identify possible spatial clusters. Finally, we used the Ordinary Least Squares and Geographically Weighted Regression models to identify mortality predictors in the territory. The mortality rate from congenital syphilis was 0.64 deaths per 1,000 live births. The distribution of deaths occurred heterogeneously, with the highest rates in the states of Pará, Acre, Rondônia, Rio de Janeiro and part of Amazonas. We identified statistically significant spatial clusters across the country, with the formation of clusters with a high-high pattern in Pará, Rio de Janeiro, and Mato Grosso (p < 0.05). We observed that the Gini index (p = 0.008; 95% Confidence Interval: 0.02–0.11), the number of nurses in primary care (p = 0.027; 95% Confidence Interval: 0.0005–0.00003) and the proportion of non-treponemal tests by pregnant women (p = 0.016; 95% Confidence Interval: 0.005–0.001) are variables that influence the occurrence of deaths. Congenital syphilis deaths in Brazil occur heterogeneously, with different rates between regions, which are geographically influenced by social and healthcare characteristics of the location.